The Little Green Data Book 2017 - World Bank (Washington, DC: World Bank, 2017)
The Little Green Data Book 2017 is based on World Development Indicators 2017 and its online database. Defining, gathering, and disseminating international statistics is a collective effort of many people and organizations. The indicators presented in World Development Indicators are the fruit of decades of work at many levels, from the field workers who administer censuses and household surveys to the committees and working parties of the national and international statistical agencies that develop the nomenclature, classifications, and standards fundamental to the international statistical system. Nongovernmental organizations have also made important contributions. We are indebted to the World Development Indicators partners, as detailed in World Development Indicators 2017 .